Character Education Values in Jambi Malay Seloko - Andryadi, Andryadi; Mutathahirin, Mutathahirin; Nurdin, Syafruddin; Baili, Baili; Ardilla, Verawati (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2025)
Traditional seloko, as part of the oral cultural heritage and local wisdom, contains moral teachings passed down from generation to generation and reflects the Jambi Malay community's outlook on life, which highly values ​​ethics and spirituality. This study aims to identify and analyze the Islamic character education values ​​contained in the traditional seloko of the Jambi Malay community and examine their relevance to character education in a modern context. The research method used is a literature study with a descriptive qualitative approach. Data were obtained from various relevant literature, documentation of traditional seloko texts, and in-depth interviews with Jambi Malay traditional figures and cultural figures to explore the philosophical meaning and educational values ​​contained therein. The analysis was conducted using a hermeneutic approach to interpret the moral and social messages implied in these traditional expressions. The results show that traditional Jambi Malay seloko is rich in Islamic character education values, such as honesty, discipline, hard work, responsibility, tolerance, mutual respect, and love of the homeland. These values ​​align with the basic principles of Islamic teachings on the development of noble morals and good behavior (akhlaq al-karimah). The relevance of these values ​​in modern character education is crucial, particularly in shaping a generation that is not only intellectually intelligent but also possesses moral integrity and social awareness.